Rapid granulation of aerobic granular sludge: A mini review on operation strategies and comparative analysis. (September 2019) - Zhang, Yihao; Dong, Xiaochuan; Nuramkhaan, Marjangul; Lei, Zhongfang; Shimizu, Kazuya; Zhang, Zhenya; Adachi, Yasuhisa; Lee, Duu-Jong; Tay, Joo Hwa
Abstract: Due to its overwhelming advantages, aerobic granular sludge (AGS) process is the most promising alternative to the conventional activated sludge (CAS) which is currently and mainly applied in wastewater treatment plants (WWTPs). Long start-up period is still one of the major challenges limiting the wide application of AGS in WWTPs worldwide. This mini review summarized the main strategies adopted in the previous works for the rapid formation of AGS, including short settling time or high selection pressure, addition of cation ions and/or coagulant or inert carrier, seeding pellets/crushed or intact granules, and inoculation of self-aggregation strain(s), etc. Comparison analysis was also performed among these strategies, with future research perspectives being prospected. Highlights: Main strategies for rapid AGS formation were summarized and reviewed. Short settling time of 0–5 min might pave the way for rapid AGS formation. Additives addition could be more efficient for rapid AGS formation. Biological components may also contribute a lot to rapid AGS formation. Scaling up the rapid AGS formation strategies in practice needs further research.